Metody i narzędzia badawcze w studiach nad rozwojem jęz yka obcego u małych dzieci - Rokita-Jaśkow, Joanna (Neofilolog, 2010)
This paper aims to present an overview of the most typical methods and tools used in studies of young children learning foreign languages. Two major groups of potential subjects have been distinguished and characterized: children learning L2 from the age of (0) 1 till 3 and from the age of 3 till 6. In the studies in the first group methods similar to studies of L1 are suggested: longitudinal case studies using observation diaries, audio- video recordings, interviews with parents, and vocabulary checklists for cross-sectional research. In the studies of older children (3-6) elicitation of language data during testing sessions is possible and recommended, for which the tools most frequently used are: imitation of a speaker, carrying out orders and using picture prompts.